European tourism demand in the face of climate change: asymmetric impacts, demand reallocation, and deseasonalisation strategies - David García-León; Nicoleta Anca Matei; Filipe Batista e Silva; Ricardo Barranco; Alessandro Dosio; Juan-Carlos Ciscar (Environmental Research Letters)
The European tourism industry, a significant contributor to employment and income, is under threat due to climate change. This study, using data from 1315 European regions and considering a tourism-specific climate index and tourism typologies, examines the potential impact of climate change on tourism demand across the continent under four warming scenarios. We find that climate change impacts in Europe will be highly asymmetrical across regions and seasons, resulting in significant reallocations of tourism demand in space and time across all warming scenarios. A clear north-south pattern in tourism demand changes emerges, with northern regions benefiting and southern regions experiencing significant reductions, particularly under higher warming. Summer demand and coastal areas, where tourism demand is more concentrated, will be particularly affected. We also quantify the deseasonalising efforts necessary to maintain the status quo in the annual demand for tourism, involving relative reductions in summer demand and increases in shoulder and winter seasons.